PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI PRISMA DAN LIMAS DENGAN PENDEKATAN RME UNTUK SISWA SMP/MTs - Yosi Srinita; Sakur Sakur; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to develop mathematics learning device that are Lesson Plan (LP) and Students Worksheet (SW) and 2013 curriculum based prism and pyramid material using the Realistic Mathematics Education (RME) approach for SMP/MTs students.This development research uses 4D development model who developed by Thiagarajan and modified by Endang Mulyatiningsih. The development carried out by the stages: (1) define; (2) design; (3) development; and (4) dessemination that is not implemented due to time and cost limitations. Data collection instrumen in this study were LP and SW validation sheets and student response questionaires. Then, learning device that had been compiled are validated by three validators and revised according to validator’s suggestions. Then, learning device that had been validated are tested in two stages, namely small group trials with the subject of six students of class VIII.B SMP Negeri 4 Tambang and a large group trial with the subject of 25 class VIII Andalusia students of SMP Juara Pekanbaru. Based on the data analysis results and the discussion it can be concluded that the 2013 curriculum based curriculum learning prism and pyramid material with a Realistic Mathematics Education (RME) approach for SMP / MTs students was considered valid with the rating average for lesson plans was 3.18 and the rating average for Students Worksheet is 3.11, and meets the practical requirements for use by the students of grade VIII SMP/MTs.Key Words: Mathematics Learning Device, Approach Realistic Mathematics Education (RME), Research and Development.